1989
DOI: 10.1093/jee/82.6.1495
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Synergism of Insecticides Against Susceptible and Pyrethroid-Resistant Third Instars of the Tobacco Budworm (Lepidoptera: Noctuidae)

Abstract: Thírd-instar tobacco budworms, Heliothis tnrescens OI' resistant to were tested exposure to residues af in scintil-lati

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Finally, it is worth noting that while pyrethroid resistance in the Australian H. armigera (33-fold) is at similar levels to that observed in Thailand populations (51-fold; Ahmad & McCaffery, 1988), these values are substantially lower than those reported from Indian populations (287-fold;McCaffery et al, 1989) and in pyrethroid resistant populations of the closely related Heliothis virescens (1000-fold; Campanhola & Plapp, 1989). Thus, caution should be used when extrapolating from studies of the evolution and management of pyrethroid resistance in Australian H. armigera to other instances of pyrethroid resistance in heliothine pest species.…”
Section: Monitoring For Resistancementioning
confidence: 59%
“…Finally, it is worth noting that while pyrethroid resistance in the Australian H. armigera (33-fold) is at similar levels to that observed in Thailand populations (51-fold; Ahmad & McCaffery, 1988), these values are substantially lower than those reported from Indian populations (287-fold;McCaffery et al, 1989) and in pyrethroid resistant populations of the closely related Heliothis virescens (1000-fold; Campanhola & Plapp, 1989). Thus, caution should be used when extrapolating from studies of the evolution and management of pyrethroid resistance in Australian H. armigera to other instances of pyrethroid resistance in heliothine pest species.…”
Section: Monitoring For Resistancementioning
confidence: 59%
“…This could be due to the intensive selection pressure of H. armigera in China with fenvalerate which has channelled the development of resistance to alpha‐cyanophenoxybenzyl pyrethroids. The lower resistance to non‐cyano phenoxybenzyl pyrethroids was also found in pyrethroid‐resistant P. xylostella 38, 39 and Tribolium castaneum Hbst 40…”
Section: Discussionmentioning
confidence: 79%
“…Also, laboratory assays have shown that chlorfenapyr is very potent against pyrethroid‐resistant strains of H. virescens 5. The origin of resistance in this strain was identified as both altered target site and metabolic 20. Pimprale et al 21 concluded, after investigating the inheritance of chlorfenapyr susceptibility in pyrethroid‐susceptible and resistant H. virescens , that one genetic factor controls both cypermethrin resistance and chlorfenapyr susceptibility.…”
Section: Discussionmentioning
confidence: 99%